ChemInform Abstract: Structures of Monomeric Octahedral D2 Rhenium(V) Oxo Complexes with Oxygen Atoms trans to the Oxo Ligands: Complexes with Methoxo Ligands trans to O(oxo). Issue 37 (September 2015) - Sergienko, V. S.; Churakov, A. V.
Abstract Review: 54 refs.